Impact of The Covid-19 Pandemic on The Effectiveness of Ship Crew Schedule at PT Surf Marine Indonesia - Putu Ayu Damayanti; Derma Watty Sihombing; Susi Herawati (Greenation International Journal of Tourism and Management, 2023)
Health is very important for all humans, because without good health it will be difficult to carry out daily activities. According to the Health Law Number 36 Year 2009 Article 1 "Health is a healthy state, both physically, mentally, spiritually and socially that allows everyone to live socially and economically productive". In the world of work, health is one of the main things that workers must have to do their work. Including in the world of shipping both on land and at sea. Workers at sea, especially ship crews at work, must be in good health so that they can carry out activities on board as much as possible. Before the ship's crew boarded the ship, the ship's crew had to do a medical check-up as a mandatory requirement to board the ship. Every three or six months the ship's crew will make a crew change because the work contract has expired and the ship will look for a replacement crew to work on the ship. During the Covid-19 pandemic, crew changes experienced obstacles because the spread of this virus was quite fast. All regions in the world are currently implementing strict health protocols to deal with the COVID-19 pandemic. Especially for ship crews, they also implement strict procedures to deal with Covid-19. During a pandemic. During this pandemic, the challenges faced by the manning division are very high where the process of changing ship crews is very difficult to carry out, while the crew on board the ship has expired. Another challenge faced when changing crews is that there is no standby crew so that the crew's working period on the ship is not in accordance with the previously agreed Sea Work Agreement.